EDUCATIONAL RESOURCES MANAGERIAL STRATEGY: FINANCIAL MANAGEMENT OF LEGAL EDUCATION BOARD (PERGURUAN TINGGI BADAN HUKUM) - wahab, abdul azis (Universitas Pendidikan Indonesia, 2018)
The emergence of the era of The Fourth Industrial Revolution (the 4.0 IR), the utilization of education resources optimally and comprehensively has a strategic and significant role in realizing the mission and objectives of higher education that maintains education as its Core Business. In order to be able to manage educational resources effectively and efficiently, appropriate managerial strategies are needed and describe actions based on goals that will be realized so as to create sustainable competitive advantages, in carrying out their programs based on managerial strategies for the use of educational resources efficiently and effectively. This study aims to analyze managerial strategies carried out by universities that have legal entities in using educational resources to support the realization of their mission. The research method used is a case study with a qualitative approach, with the object of research being universities that have legal entities, with the research sample being UPI PTN-BH. The managerial strategy of financial management of all activities is based on internet media (on-line), both in terms of planning, implementation, supervision and reporting. However, it needs to be improved in relation to the competence of the implementing staff in accordance with the needs and demands relating to the applicable financial information technology, in streamlining and streamlining the work patterns that must be applied.Keywords: Financial management, managerial strategies, educational resources